1998
DOI: 10.3189/1998aog27-1-603-609
|View full text |Cite
|
Sign up to set email alerts
|

Surface energy balance and meltwater production for a Dry Valley glacier, Taylor Valley, Antarctica

Abstract: ABSTRACT. The surface energy bal ance was calcul ated to estimate sublim ati on and melt on the surface a nd terminus of Canada Glacier, Taylor Vall ey, Antarctica, during the 1 994~95 a nd 1 995~96 austral summers. Our resul ts indicate th at sublimati on accounted for roughly 80 % of the obse rved 1 994~95 summ er a bl ation a nd 40 % of the obse rved 1 995~96 summer ablati on on the surface of the glacier. Sublim ation on the termi nus cl iffs appears to be less significant tha n sublimation on the glacier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 7 publications
7
71
2
Order By: Relevance
“…During warm austral summer months, this accumulated supply of subsurface ice melts and seeps to the surface, and could generate some of the liquid water we observed. It is not clear, however, whether this source alone could supply the amount of water observed, as loss by sublimation would be quite high (Clow et al, 1988;Lewis et al, 1998;Gooseff et al, 2003). How much melt could be recharged by this process is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…During warm austral summer months, this accumulated supply of subsurface ice melts and seeps to the surface, and could generate some of the liquid water we observed. It is not clear, however, whether this source alone could supply the amount of water observed, as loss by sublimation would be quite high (Clow et al, 1988;Lewis et al, 1998;Gooseff et al, 2003). How much melt could be recharged by this process is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Lewis et al, 1998;Hoffman et al, 2008;MacDonell et al, 2012). Surface energy balance studies have all shown the dominance of sublimation on ice surfaces in this region, and have intimated that not only is melt restricted to approximately two months in the austral summer, but within this period, melting is episodic and spatially constrained (Lewis et al, 1998;Hoffman et al, 2008). Melt at the surface is often restricted to areas where albedo is lowered due to the incorporation of sediment (e.g.…”
Section: Comparison Of Ablation Results With Other Studiesmentioning
confidence: 99%
“…Second, subsurface melting occurs during windy, sunny days by a solid-state greenhouse effect (17,18), even with air temperatures below freezing. In addition, turbulent heat transfer in the Dry Valleys is relatively large and keeps ice surfaces cool (18,19). Thus, a drop in wind speed reduces latent and sensible heat losses such that ablation shifts from sublimation-dominated to melt-dominated (increases in downslope winds also can warm the valleys to melting temperatures, but such winds are infrequent in summer when melting takes place).…”
Section: Discussionmentioning
confidence: 99%